Public opinions of a judge in defence of the rule of law: transformation of the right to freedom of expression into an ethical and legal duty to speak out in defence of fundamental values - Pilkov , Kostyantyn (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
The perspectives on the individual role of a judge in safeguarding judicial independence and, more broadly, the foundational principles that sustain the rule of law have been evolving for the last two decades. In response to recent challenges, when judges from different countries, feeling a moral obligation to speak out in defence of democratic values, made critical public statements, international jurisdictional bodies and judicial organisations also responded to these new challenges and developed new approaches to the ethical limits of public expression by judges.This article seeks to examine whether the traditional emphasis on ethical constraints in any political pronouncements by judges remains in place and whether the ethical guidelines for judges regarding public statements remain unchanged. Additionally, it considers whether there are grounds to discuss the existence of a positive obligation for judges to speak out in certain cases.The article indicates a gradual shift away from the concept of a purely institutional and collective responsibility of the judicial system for the preservation of judicial independence. The author presents the argument that each judge is ethically, if not legally, obliged to defend it. At the same time, it is not only about the protection of independence by an individual judge in a situation that concerns only that judge, but also about the protection of judicial independence on the scale of the entire judicial system. The approach to the substance of public statements by judges in defence of the rule of law and judicial independence is also evolving. There is a shift from an emphasis on restraint and the limited permissibility of comments on controversial political issues to a stance of 'fearlessly defending the position' and 'clear and convincing statements' about the judiciary's opposition to government proposals that tend to undermine judicial independence.Furthermore, the author observes that in the recent case law of the ECtHR, the ethical and legal duty of a judge to speak out in defence of the rule of law and judicial independence is still regarded as primarily a moral obligation. This encourages judges to exercise their right to freedom of expression through critical public statements. The article nevertheless acknowledges that when making public statements in defence of the fundamental values of a democratic society, judges remain subject to ethical constraints. Such restrictions include the requirements of political neutrality (in the narrow sense of ideological or party neutrality, but not neutrality in the sense of absence of criticism), as well as the unacceptability of manifestations of bias in pending cases, or questioning the res judicata of court decisions or otherwise damaging the authority of the judiciary.